Procedural aspects of international commercial arbitration - Vach, Jakub; Boháček, Martin, 1947-; Nováková, Tereza; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This diploma thesis deals with the international commercial arbitration. The aim of the diploma thesis is to identify and evaluate the international commercial arbitration with a focus on the definition of international commercial arbitration, the legal regulations governing the international commercial arbitration and the discovery of differences between arbitration rules of The International Court of Arbitration of the International Chamber of Commerce and London Court of International Arbitration using comparison, the agreement to arbitrate, the appointment and the rights and duties of the arbitrator, the proceedings of international commercial arbitration and the arbitral award. The methods used to develop this diploma thesis are analysis, comparison, description, and synthesis.
Vedoucí práce: Martin Boháček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses